Possibility of producing ethanol from moringa oleifera press cake - Umarul Imran, Amran (2014)
In recent decades is the energy crisis and environmental issue become critical problem in the world. The cause depleting the reserved of fossil fuel, therefore the people start find the alternative fuel to replace fossil fuel. Many research have been done to find alternative fuel to fulfill increasing energy demand. Recently, biofuel (bioethanol) had been proposed as replacement of fossil fuel. There are countless raw materials that can be used to produce ethanol such as jatropha cakes, castor cakes, palm oil cakes and Moringa oleifera cakes. The Moringa oleifera is multifunctional used plant. From leaves until roots of Moringa oleifera plant can give benefit to a human. The Moringa oleifera also known as miracle tree. The composition of Moringa oleifera press cake is quite similar with composition of jatropha such as cellulose, hemicellulose, lignin and other compositions. That means the Moringa oleifera press cake also can produce ethanol. In order to produce ethanol from press cake, the following step must be followed, pre-treatment with dilute acid to break down the cellulose of press cake, acid hydrolysis for converting the cellulose to simple sugar like glucose and fermentation by using Saccharomyces cerevisiae to produce ethanol. The parameters involved in this study is concentration of acid during hydrolysis with 2%, 4% and 6% of sulphuric acids, different of mass yeast with 2g, 4g and 6g and different period of fermentation with 3 days, 5 days and 7 days. Based on the result obtained, the increasing of concentration acid during hydrolysis giving the low concentration of ethanol. For mass of yeast, the best yield was at 2g and the lowest yield was at 6 g. For period fermentation, the amount of ethanol was decreased if the period of fermentation taking longer.